2017
DOI: 10.1111/ecca.12253
|View full text |Cite
|
Sign up to set email alerts
|

House Prices, Wealth Effects and Labour Supply

Abstract: We examine the impact of house prices on labour supply decisions using UK microdata. We combine household survey data with local‐level house price measures and controls for local labour demand. Our microdata also allow us to control for individual level income expectations. We find significant house price effects on labour supply, consistent with leisure being a normal good. Labour supply responses to house prices are concentrated among young married female owners and older owners. This finding suggests that h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 33 publications
2
22
0
Order By: Relevance
“…The literature has shown that increases or expected future increases in wealth lead agents to reduce the hours they work (Joulfaian and Wilhelm ; French and Cheng ; Imbens et al . ; Disney and Gathergood . We show that when individuals reduce the hours worked before retirement in response to an increase in the expected age of retirement, for zero or small negative cross derivatives of the the utility function with respect to consumption and leisure, the decrease in saving is far larger than if they worked the same hours as before.…”
Section: Introductionmentioning
confidence: 79%
“…The literature has shown that increases or expected future increases in wealth lead agents to reduce the hours they work (Joulfaian and Wilhelm ; French and Cheng ; Imbens et al . ; Disney and Gathergood . We show that when individuals reduce the hours worked before retirement in response to an increase in the expected age of retirement, for zero or small negative cross derivatives of the the utility function with respect to consumption and leisure, the decrease in saving is far larger than if they worked the same hours as before.…”
Section: Introductionmentioning
confidence: 79%
“…In addition, some similar research (Disney and Gathergood, ; He, ; Johnson, ) used house value to investigate the effect of house price variations on labour supply. In the context of China, house price appreciation is the major component of house value (Gan, ).…”
Section: Results and Robustness Checksmentioning
confidence: 99%
“…Henley () found significant reductions in working hours for both men and women in response to housing capital gains. Disney and Gathergood () found that the wealth effect generated from increasing house prices significantly reduced labour force participation (LFP) in the UK. However, Johnson () found little evidence of a positive relationship between house prices and LFP of married women in a US metropolitan area.…”
Section: Introductionmentioning
confidence: 99%
“…We extend the standard two-period life-cycle model of Rossi and Trucchi (2016) to a three-period set-up and, following Hurst and Stafford (2004) and Bhutta and Keys (2016), explicitly incorporate home ownership, mortgage borrowing, house price appreciation, home equity extraction, and collateral constraints to capture the key features of the Texas housing 7 A more distinct stream of research has explored the relationship between the broader housing market and labor supply, generally finding negative wealth effects of house price growth, consistent with leisure being a normal good (Atalay, Barrett, & Edwards, 2016;Disney and Gathergood, 2013;Milosch, 2014;Fu, Liao, & Zhang, 2016;Bottazzi, Trucchi, & Wakefield, 2017;Zhao and Burge, 2017). But a consensus on the effect of house price growth on labor supply remains elusive.…”
Section: Theoretical Frameworkmentioning
confidence: 99%